Pengaruh Social Media Influencer dan Persepsi Kualitas Produk terhadap Minat Beli dengan Kepercayaan Merek sebagai Variabel Moderator - Adinda Dwi Ariyanti (Literasi : Jurnal Kajian Keislaman Multi-Perspektif, 2025)
The rapid development of the cosmetics industry and the increase in social media users have encouraged companies to utilize influencers as a marketing strategy. This study aims to analyze social media influencer and product quality perceptions on the purchase intention of Hanasui product with brand trust as a moderator. This study uses a quantitative approach by conducting a questionnaire ti 146 respondents. The result show that social media influencer and product quality perceptions have a pocitif and significant effect on putchase intention. Bbrand trust was found to moderate the relationship between social media influencer and purchase intentions with a weak effect, while teh relationship between product quality perceptons and purchase intention didn’t show significant effect. The result empharuze the important of influencer stratef=gy management and strengthening brand trsut in increasing customer purchase intention.